Central fatigue and neurotransmitters, can thermoregulation be manipulated? - Meeusen, R.; Roelands, B. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Fatigue is a complex phenomenon that can be evoked by peripheral and central factors. Although it is obvious that fatigue has peripheral causes such as glycogen depletion and cardiovascular strain, recent literature also focuses on the central origin of fatigue. It is clear that different brain neurotransmitters - such as serotonin, dopamine and noradrenaline - are implicated in the occurrence of fatigue, but manipulation of these neurotransmitters produced no conclusive results on performance in normal ambient temperature. Exercise in the heat not only adds an extra challenge to the cardiorespiratory system, but also to the brain. This provides a useful tool to investigate the association between exercise-induced hyperthermia and central fatigue. This review focuses on the effects of pharmacological manipulations on performance and thermoregulation in different ambient temperatures. Dopaminergic reuptake inhibition appears to counteract hyperthermia-induced fatigue in 30 °C, while noradrenergic neurotransmission shows negative effects on performance in both normal and high temperature, and serotonergic manipulations did not lead to significant changes in performance. It is, however, unlikely that one neurotransmitter system is responsible for the delay or onset of fatigue. Further research is required to determine the exact mechanisms of fatigue in different environmental conditions.